The Improvement of Cognitive Function and Decrease the Level of Stress in the Elderly with Brain Gym - Lilik Marifatul Azizah; Tri Martiana; Oedojo Soedirham (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
The decline in cognitive function in the elderly, which is part of the aging process can result in long-term memory problems and information processes, so it is often regarded as a stressor that causes stress and perceived as an adverse threat. Brain gym can improve memory, decreased emotional stress and the clearer mind. The aim of the study analyzed the effectiveness of brain gym in improving cognitive function and decreased the level of stress of elderly. Pre-experimental study of one group pretest-posttest design with 35 samples selected by simple random sampling. The frequency of Brain Gym exercise twice a week with duration of every 15 minutes and done in four weeks. Measurement of stress level using DASS, while Cognitive function with MMSE. Data analyzed using Wilcoxon signed rank test. The results showed improvement of cognitive function in elderly and decreased stress level after brain gym (p = 0.001 and p = 0.009 at Î± = 0.05). Brain gyms are more effective at lowering stress levels than older cognitive function improvements that require longer and more intense time to improve concentration and elderly memory. Keywords: Brain Gym, Kognitif, Stress, Elderly